Improving Social Studies Learning Outcomes Through Project-Based Blended Learning Assisted By Scrapbooks In Grade IV Students - Atmini, Tri; Zulfiati, Heri Maria; Widiyaningsih, Nunuk; Erniasari, Erniasari; Pamungkas, Fajar Satriya (Universitas Sarjanawiyata Tamansiswa, 2023)
This study aims to (1) determine the application of the project-based blended learning method on improving student learning outcomes in social studies learning material for Class IV Economic Activities Semester I at SD Negeri Nglindur, Girisubo District, Gunung Kidul Regency, and (2) determine the effectiveness or not of the use of project based blended learning methods assisted by scrapbook on student learning outcomes in social studies learning material Economic Activities Class IV Semester I at SD Negeri Nglindur, Girisubo District, Gunung Kidul Regency. This type of research is descriptive qualitative. The study population is all Grade IV elementary school students at SD Negeri Nglindur in 2023/2024 consisting of 12 students. Data collection using tests, observations, and documentation. The results of this study show that (1) the application of the project-based blended learning method is effective in improving student learning outcomes in social studies learning material for Class IV Economic Activities in the first semester at SD Negeri Nglindur, Girisubo District, Gunung Kidul Regency, (2) the application of the project-based blended learning method assisted by scrapbook improve student learning outcomes in social studies learning material for Class IV Economic Activities Semester I at SD Negeri Nglindur, District Girisubo, Gunung Kidul Regency.